Fabrication and characterization of novel antimicrobial thin film nano‐composite membranes based on copper nanoparticles - Yahia Cherif, Asma; Arous, Omar; Mameri, Nabil; Zhu, Junyong; Ammi Said, Abdallah; Vankelecom, Ivo; Simoens, Kenneth; Bernaerts, Kristel; Van der Bruggen, Bart (Journal of chemical technology and biotechnology (1986), 2018)
BACKGROUND Copper nanoparticles (CuNPs) are studied for the design of advanced nanocomposite membranes owing to their highly antimicrobial properties, specific catalytic and chemical activities, abundancy and low cost. In this work, thin film nanocomposite membranes (TFN) containing CuNPs in the polyamide (PA) layer were designed via a facile interfacial polymerization method. The nanoparticles were incorporated into an aqueous solution containing piperazine monomers which is poured on the top surface of the polyethersulfone ultrafiltration membrane followed by adding trimesoyl chloride to form a polymerized PA film. RESULTS The results show that the surface morphological structure investigated by scanning electron microscopy and atomic force microscopy images is subject to visible changes of surface morphology, with a rougher net‐like structure while analysis of the chemical structure using attenuated total reflection–Fourier transform infrared spectroscopy confirms that the introduction of CuNPs did not impede the structure of the PA layer. The effect of addition of inorganic functionalized nanomaterials on the overall membrane performance was significant. The water flux was greatly increased (twice the original water permeability), while maintaining high retention of Na2SO4, demonstrating good performance in the range of nanofiltration (NF). Furthermore, the TFN membranes exhibited a specific antibacterial effect, reducing the number of living bacteria (Escherichia coli) by 94.0%. CONCLUSION Inorganic functionalization using CuNPs in the aqueous phase strongly enhanced membrane performance and provided the membrane surface with antimicrobial properties. This study suggests a new approach to TFN membrane research for the design of NF membranes for water treatment. © 2018 Society of Chemical Industry